Peer Counseling: Method, Metaphor, or Mindset? - Jordan, Leonora Micah (Frontiers in Rehabilitation Sciences, 2022)
Keywords Peer Counseling, Peer Support, counseling method, self help, Independent Living, expert by experience, Ergänzende unabhängige Teilhabeberatung, EUTB, Additional Independent Participation Consulting, ableism, agency Abstract Peer Counseling and Peer-to-Peer-Counseling are two common counseling formats worldwide where people meet each other at eye level. Rooted in the Independent Living and Self-Help Movement, "classic" Peer Counseling can be considered as a professional counseling service offered by and for people with disabilities. In this article, the question is explored whether Peer Counseling is far reaching than just being labeled as a counseling method. In many countries, it has now found a permanent place in the counseling landscape among others. Furthermore, the question arises whether it does not also serve as a metaphor for a self-determined way of life. In addition, in this article it will be worked out whether and why the mindset, the attitude, is also important in professional Peer Counseling. Since 2018, Peer Counseling has been offered at over 500 counseling centers in Germany as part of the "Ergänzende unabhängige Teilhabeberatung – EUTB®" (Additional Independent Participation Consulting). At a low-threshold and accessible level, advice seekers can find competent individual-centered professional counseling here – often from experts by experience: peers. For many people seeking advice, this is the first and last point of contact for all matters relating to rehabilitation, inclusion and social participation. As part of my PhD-project, I am doing research on Peer Counseling and parallel to this, I train EUTB- and Peer Counselors. Peer Counseling actually is (much more than) a counseling approach which represents a true enrichment for everyone.